Time Spent on the Internet and Adolescent Blood Pressure. (October 2015) - Cassidy-Bushrow, Andrea E.; Johnson, Dayna A.; Peters, Rosalind M.; Burmeister, Charlotte; Joseph, Christine L. M.
Internet use is nearly ubiquitous among adolescents. Growing evidence suggests heavy Internet use negatively impacts health, yet the relationship between time spent on the Internet and adolescent blood pressure (BP) is unknown. We examined the association between Internet use and elevated BP in a racially diverse cross-sectional sample of 331 healthy adolescents (ages 14–17 years). Heavy Internet use was defined as ≥2 hr/day, moderate use as <2 hr/day and ≥5 days/week, and light use as <2 hr/day and ≤4 days/week. Elevated BP was defined as systolic or diastolic BP ≥90th percentile. Heavy Internet users had statistically significantly higher odds of elevated BP compared to light Internet users. School nurses can play an important role in preventing high BP through assessment of BP and other health behaviors including Internet use, and health teaching to individuals, student groups, faculty, and parents to increase awareness of the relationship between Internet use and health.